2003
DOI: 10.1007/s00415-003-0256-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of complex movements reflects dysfunction in Huntington?s disease

Abstract: Results of various complex instrumental tools, rating scales, caudate atrophy and CAG repeat length may reflect the severity of Huntington's disease (HD). A simple assessment task for dysfunction due to disease is the standardized, computer based performance of peg insertion. The objectives of our study were to compare scored HD symptoms, computed bicaudate diameter ratio (BDR), age related genetic disease load (CAG index = [CAG-35.5 x age]) and peg insertion scores between asymptomatic 34 HD gene carriers, 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 29 publications
5
19
0
1
Order By: Relevance
“…A further trial that investigated the impact of transdermal rivastigmine administration on motor performance with an altered standardized peg insertion paradigm showed that patients with predominant cholinergic neurodegeneration need longer for performance of the peg insertion paradigm in comparison with controls. Thus this study confirms a deterioration in carrying out of complex motion series in neurodegenerative processes, because this was also shown in disorders with preponderant functional basal ganglia disturbances, ie, Huntington’s disease or PD (Müller et al 2000; Saft et al 2003, 2004). This trial also confirmed that assessment of co-ordinated movements with the non-dominant hand better reflects disturbances of fine motor behavior during neurodegeneration probably due to regular training and use (Müller et al 2000, 2003b; Pal et al 2001; van Vugt et al 2001; Saft et al 2003, 2004).…”
Section: Rivastigmine and Its Impact On Motor Behavior In Ad And Pdsupporting
confidence: 82%
See 1 more Smart Citation
“…A further trial that investigated the impact of transdermal rivastigmine administration on motor performance with an altered standardized peg insertion paradigm showed that patients with predominant cholinergic neurodegeneration need longer for performance of the peg insertion paradigm in comparison with controls. Thus this study confirms a deterioration in carrying out of complex motion series in neurodegenerative processes, because this was also shown in disorders with preponderant functional basal ganglia disturbances, ie, Huntington’s disease or PD (Müller et al 2000; Saft et al 2003, 2004). This trial also confirmed that assessment of co-ordinated movements with the non-dominant hand better reflects disturbances of fine motor behavior during neurodegeneration probably due to regular training and use (Müller et al 2000, 2003b; Pal et al 2001; van Vugt et al 2001; Saft et al 2003, 2004).…”
Section: Rivastigmine and Its Impact On Motor Behavior In Ad And Pdsupporting
confidence: 82%
“…Thus this study confirms a deterioration in carrying out of complex motion series in neurodegenerative processes, because this was also shown in disorders with preponderant functional basal ganglia disturbances, ie, Huntington’s disease or PD (Müller et al 2000; Saft et al 2003, 2004). This trial also confirmed that assessment of co-ordinated movements with the non-dominant hand better reflects disturbances of fine motor behavior during neurodegeneration probably due to regular training and use (Müller et al 2000, 2003b; Pal et al 2001; van Vugt et al 2001; Saft et al 2003, 2004). An improved brain plasticity of the dominant brain hemisphere with secondary better compensation of motor deficits may additionally be responsible for the inferior sensitivity of the applied instrumental paradigm to reflect motor disturbances of the upper limb during a neurodegenerative process (Van Hilten et al 1993; Müller et al 2000, 2003b; van Vugt et al 2001; Ioffe 2004; Saft et al 2004).…”
Section: Rivastigmine and Its Impact On Motor Behavior In Ad And Pdsupporting
confidence: 82%
“…22 In this study, the CAG index ranged from 29.5 to 666.5 (mean (SD) 363 (136)). The controls had no history of a neurological or psychiatric disorder.…”
Section: Participantsmentioning
confidence: 67%
“…Hence, the patients with Huntington's disease showed significantly greater activation than controls bilaterally in the caudal anterior cingulate gyrus, right dorsal premotor cortex, right inferior frontal gyrus, left middle frontal gyrus, and left superior parietal lobule. As our aim was to examine prefrontal connectivity, we selected peak voxels from these activation results within the anterior cingulate (left/right: coordinates (mm) ¡10, 38,22) and lateral prefrontal regions on the border of inferior and middle frontal gyri (left/right: coordinates (mm) ¡38, 44, 16) to model prefrontal functional connectivity (fig 3). ROIs were defined as 6 mm diameter spheres centred on the selected peak voxels.…”
Section: Roi Selectionmentioning
confidence: 99%
“…Huntington's disease or PD. 1,9 This instrumental tool was sensitive enough to reflect the antiparkinsonian efficacy of a single administration of levodopa/decarboxylase inhibitor formulation and or of daily amantadine sulphate infusions during an interval of three days in PD patients. 2,4,10 In these trials, we avoided the comparison against placebo intake, which may also stimulate the nigrostriatal system due to release of dopamine and thus may confound the rating and motor test outcomes.…”
Section: Introductionmentioning
confidence: 99%